Germinación de semillas de orquídea cattleya maxima mediante técnicas de laboratorio - Serrano Rogel, Pamela Yamileth (2011)
In the laboratory of Biotechnology, Faculty of Agricultural Sciences was carried out this research, whose stated objectives were to determine the appropriate composition of culture medium for in vitro seed germination of Cattleya maxima, assessing the best protocol for obtaining Cattleya maxima with the results. Capsules were obtained Cattleya maxima, which were collected closed at its mature stage, they present the phenomenon of dehiscence to avoid future contamination in the culture media. They were then transported to the laboratory for washing with distilled water and detergent and then bathe in alcohol and flamed. Then we proceeded to dissect the capsule with the help of the mini knife planted in the culture medium which was enriched with Knudson salts supplemented with 100% activated carbon, l-cysteine, coconut water, sugar and agar, adjusting to a pH of 4.8. The experimental design was completely randomized blocks with ten treatments (culture medium) and five replicates per treatment (bottles), totaling 50 experimental units. This research concluded that, Knudson basal medium enriched with 100% activated carbon at concentrations of 1 g / l and 1.5 g / l speed in vitro germination of seeds of Cattleya maxima, this study describes a protocol that thousands of seedlings can develop excellent vegetative growth, from a capsule of this important orchid. This protocol is a model for conserving species that are endangered.